Sistema web de gestión de farmacia, basado en tecnología móvil para el Hospital Básico 7 B.I Loja. - Valdez Masache, Angel Alberto (2016)
This research related to the Web Pharmacy Management System is based on creating a standard technology for health care providers and services. It was designed specifically for allowing the pharmacy to better enhance its effectiveness and allows users to meet the daily objectives of customer care and pharmaceutical efficiency in a basic hospital and nursing health care environment. The development, methodology and implementation of this system were applied to Windows XP and have been designed specifically for use in the basic hospital or mobile health care setting. It allows for an interactive program that gives instruction and feedback to users as well as direction on proper and appropriate usage. RUBY programming language was used in the development of this software system. Additionally, framework on the RAILS was utilized which allows and gives freedom to develop and expand this particular form of information technology. This system is easily integrated into Javascript, CSS, JQUERY, Sublimetext, Sourcetree, Github, Digital Ocean, Bootstrap and HTML which are the foundational bases of current pharmacy technologies in Ecuador. Bootstrap is a technology framework which allows for the adaptation and utilization of mobile devices so that user functionability can be achieved in any health care setting. In order to accommodate this research, the current pharmacy management system in use was studied in order to determine a solution that best meets the needs of consumers and pharmacy users. A daily report on its functionability ensures that the system continuously maintains integrity, allows for corrections and additions when needed, and gives superior customer service throughout its use.